172 'Can't somebody do something? …there must be someone who can help?' Results of a survey of a regional multidisciplinary working party of the fundamental aspects of assessment of sialorrhoea in patients with progressive neurological disorders to support personalised care. (14th March 2023) - Jones, Sophie; Erridge, Clare; Guest, Annie; Quinn, Tina; Curtis, Matthew
Abstract : Background: Sialorrhoea is a common symptom of progressive neurological conditions, causing a significant burden for patients and their care givers. A previous survey showed healthcare professionals felt drug interventions provided insufficient control. This symptom benefits from holistic and multidisciplinary assessment and management. This work aims to identify the key components of a clinical assessment, from a multidisciplinary perspective, with the intention of supporting delivery of personalised and effective care of this symptom. Methods: Motivated by poor outcomes of management of this symptom, a regional specialist working party was convened. These multidisciplinary professionals, with expertise in sialorrhoea management, completed a survey to identify which factors enhanced assessment of issues related to sialorrhoea and how management is impacted. Responses were compared against established saliva assessment tools. Results: Twelve professionals completed the survey: Responses were analysed and grouped into 5 themes. No theme was unanimously identified by all responders. The most common (83%) was assessing response to previous strategies, 75% focused on the saliva itself, 67% on functioning, 50% on psychosocial impact and 50% on physical assessment. Qualitative responses were collected on the above themes and their impact on management, notably highlighting the benefit of more detailed psychosocial and functional assessment. The themes were not routinely covered in available tools. Where overlap exists, such as functioning and psychosocial impact, the survey responses exceeded elements within the tools. Conclusion: The results show each theme identified was not covered by all professional groups, indicating benefit from multidisciplinary assessment. A standardised approach, encompassing all that has been discovered in this work would streamline assessment, minimising burden to patients. This would support professionals to develop wider skills in assessment from their multidisciplinary colleagues. The working group will now develop this resource to guide professionals with the optimal assessment and then evaluate the impact on patient outcomes regionally.